APLIKASI BEBERAPA JENIS NUTRISI DENGAN SUBSTRAT BERBEDA PADA HIDROPONIK RAKIT APUNG BAYAM BRAZIL - Jemamu, Karolina; Astutik, Astutik; Anggarbeni, Susilo Ribut; Sumiati, Astri (Universitas Tribhuwana Tunggadewi, 2025)
This study aimed to investigate the impact of various substrates and nutrients on the growth and yield of Brazilian spinach (Alternanthera sissoo) in a floating raft hydroponic system. The research was used a factorial Completely Randomized Design (CRD) with two factors: substrate type (M) consisting of rice husk charcoal, sphagnum moss, and compost; and nutrient type (A) comprising AB Mix, NPK, and Gandasil D. There were 9 treatment combinations, each replicated 3 times, resulting in a total of 81 plant samples. The observed parameters included time to sprouting, plant height, number of leaves, number of branches, canopy diameter, fresh weight, and dry weight of the plant. The results showed a significant interaction between substrate and nutrient types on the number of branches at 6 weeks after planting, while no interaction was observed for other parameters and the best results were obtained from the combination of rice husk charcoal substrate and AB Mix nutrient. Substrate and nutrient types significantly affected plant growth (height, number of branches, and canopy diameter) and yield (fresh and dry plant weight as well as fresh and dry root weight). Rice husk charcoal and AB Mix nutrient produced the best plant growth and yield up to 6 weeks after planting.